(untitled) (American Journal of Islam and Society, 1992)
We live in a world of nation-states where national cohesiveness constitutes the legitimizing ground for political unity. In such a world, multinational political units are considered to be peculiar entities whose existence is either taken as an exception to the rule or is considered to be transient and therefore destined to collapse into its national units. A product of Eutope’s historical experience, nationalism found its way to the Muslim world and gained many adherents and advocates in its ethnic (i.e., Arabic, Turkish, Kurdish) and religious (i.e., Pakistani, Iranian) forms. The nationalistic mindset has become an intrinsic part of the political thinking of many Muslim individuals and groups. As a result of the discontinuity in historical political thinking and practice effected by the European cultural and political domination of Muslim life for the last two centuries, many Muslims are unaware of the much superior political structutes which existed-albeit in rudimentary, distorted, or compromised forms-before Westem penetration. In this paper, I will discuss the origin and development of the concept of nationalism, underscore its defects, and point out some of its devastating consequences, especially in regions rich in ethnic and religious minorities. I argue that nationalism is a European phenomenon invented by German intellectuals and employed by Prussia in order to bring about a united German state. I contend that a national govemment tends to suppress minority groups and is therefore inappropriate to societies with heterogenous and diverse populations. I conclude by discussing, in general terms, the model of communal pluralism that flourished under the khilafah system. The Genesis of Nationalism Nationalism is a relatively modem political doctrine. Writers on nationalism trace it back to Rousseau, a European philosopher who insisted that a good political community was characterized by a homogeneous population. However, nationalism as we know it today began to take shape not in France, but in Germanic Prussia. German writers interested in a united German state began to advocate nationalism as the only legitimate basis for statehood ...